O05 1-YEAR RESULTS OF AN INTERNATIONAL RANDOMIZED CONTROLLED TRIAL (ESTOIH STUDY) COMPARING THE "SHORT STITCH" VERSUS "LONG STITCH" TECHNIQUE USING AN ULTRA-LONG ABSORBABLE ELASTIC SUTURE MATERIAL. (25th November 2021) - Fortelny, René; Albertsmeier, Markus; Hofmann, Anna; Riedl, Stefan; Kewer, Jan Ludolf; Shamiyeh, Andreas; Maier, Theo David; Schuhmacher, Guido; Koeckerling, Ferdinand; Pession, Ursula
Abstract: Aim: The aim of this multicenter, randomized, double blinded study was to compare the short stitch technique for elective, primary, median laparotomy closure with the long stitch closure using the ultra-long absorbable, elastic monofilament suture made of poly 4-hydroxybutyrate (MonoMax®). Material and Methods: Eligible patients were randomly allocated to receive either the short or the long stitch suture technique in a 1:1 ratio in 9 centers in Austria and Germany after elective midline laparotomy. Results: 425 patients were randomized to receive either the short stitch (n = 215) or long stitch technique (n = 210). In a cox proportional hazards model, the risk for burst abdomen was reduced by 7-fold (HR 0.183 (0.0427 - 0.7435), p = 0.0179) for the short stitch group. Complications such as seroma, hematoma and other wound healing disorders occurred without significant differences between groups. After one year, the incisional hernia rate was 3.65% in the short stitch group compared to 8.80% in the long stitch group (p = 0.055). The combination of burst abdomen and incisional hernia rate had a significantly lower rate of 5.38% for the short stitch technique compared to 13.17% for the long stitch technique (p = 0.0142). Conclusions: Both in the short-term results, the short-stitch technique showed substantial advantages in burst abdomen rate, as well as in the 1-year follow-up regarding the incidence of incisional hernias. The low incidence of incisional hernia in the short stitch technique with MonoMax® is promising in comparison to previously published data and should be confirmed in the 3-year follow-up.